2015
DOI: 10.1111/joid.12041
|View full text |Cite
|
Sign up to set email alerts
|

Ruling on the Profession: Interior Design in the Courts

Abstract: This paper uses the legal story of an interior design practitioner, Florence Karasik, as a basis for a broader discussion of the professionalization of interior design. The Karasik case will demonstrate three things: (1) that law, which is largely neglected in histories of professionalism, is an important barometer for shifting opinions about what it means to be a profession; (2) that everyday people, like Florence Karasik, had their own, popular conceptions of interior design as a profession; and (3) that pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Likewise, through a detailed case study analysis, Erin Cunningham pieces together the legal turmoil of an individual designer to clarify the state's “increasingly decisive role in determining the professional status of interior design” in the United States (Cunningham, , p. 25). How might this story encourage the consideration of a future scenario that depicts design professions that have merged or lost their discreet identities?…”
mentioning
confidence: 99%
“…Likewise, through a detailed case study analysis, Erin Cunningham pieces together the legal turmoil of an individual designer to clarify the state's “increasingly decisive role in determining the professional status of interior design” in the United States (Cunningham, , p. 25). How might this story encourage the consideration of a future scenario that depicts design professions that have merged or lost their discreet identities?…”
mentioning
confidence: 99%
“…Data from this research has also shown that participants understand the importance of clear definitions in the process of professionalization, as stated by many as the important step in formalizing the profession (Belis et al, 2014;Cunningham, 2015;Dawkins, 2014;Dickson & White, 1997;Dickson & White, 1994;Guerin & Martin, 2004;Havenhand, 2004;Martin, 1999;Puzzuoli, 2003;Wheeler, 1895;White, 2009;Whitney, 2008). However, it is also clear that participants themselves were unsure of the definitions of the professions.…”
Section: Future Researchmentioning
confidence: 60%
“…Florence Karasik was a professional interior designer practicing out of her home in Rumson, New Jersey. She had been running her business out of her home for three years before she was barred from practicing by building inspector Joseph Ciejka with a zoning ordinance claiming her business was not a profession (Cunningham, 2015). She took the cause to court, and the judge agreed that her business was not professional based on her advertising herself as an interior decorator within the telephone directory (the only descriptor available for her to use), and the fact that she conducted sales making her not a professional but a businesswoman, and businesses…”
Section: Section Four: the Consequences Of Gendering The Interior Des...mentioning
confidence: 99%
See 2 more Smart Citations